Exploring the Impact of COVID‐19 on Employees' Boundary Management and Work–Life Balance. (19th July 2022) - Adisa, Toyin Ajibade; Antonacopoulou, Elena; Beauregard, T. Alexandra; Dickmann, Michael; Adekoya, Olatunji David
Abstract: The COVID‐19 pandemic altered the ways academics work and live by creating a context during the spring of 2020 when working from home was largely mandatory and where, for cohabiting workers, the home as workplace was simultaneously occupied by all household members during working hours (and beyond). Using a multi‐method qualitative approach, we examine how academics experienced working from home during the unprecedented circumstances imposed by the first UK lockdown and social distancing measures. Our findings show that a working arrangement commonly termed 'flexible' – working from home – can actually reduce flexibility in a context of mandatory implementation, accompanied by the removal of instrumental and emotional support structures such as childcare and face‐to‐face (physical) social gatherings. Intensified workloads, increased employer monitoring, social disconnection and blurred boundaries between work and personal life collectively generate the reduction of employees' perceived flexibility‐ability. Experiences may be particularly negative for those with low flexibility‐willingness, whose pre‐pandemic preference was to separate work and home as much as possible. Employee efforts to assert agency in this context include establishing 'micro‐borders' and using time‐based strategies to create 'controlled integration'. We discuss implications for border theory and outline directions for future research.